Nurse-led, screening-triggered, early specialised palliative care intervention programme for patients with advanced lung cancer: study protocol for a multicentre randomised controlled trial. Issue 11 (26th November 2020) - Fujisawa, Daisuke; Umemura, Shigeki; Okizaki, Ayumi; Satomi, Eriko; Yamaguchi, Takuhiro; Miyaji, Tempei; Mashiko, Tomoe; Kobayashi, Naoko; Kinoshita, Hiroya; Mori, Masanori; Morita, Tatsuya; Uchitomi, Yosuke; et al.
Abstract : Introduction: It has been suggested that palliative care integrated into standard cancer treatment from the early phase of the disease can improve the quality of life of patients with cancer. In this paper, we present the protocol for a multicentre randomised controlled trial to examine the effectiveness of a nurse-led, screening-triggered, early specialised palliative care intervention programme for patients with advanced lung cancer. Methods and analysis: A total of 206 patients will be randomised (1:1) to the intervention group or the control group (usual care). The intervention, triggered with a brief self-administered screening tool, comprises comprehensive need assessments, counselling and service coordination by advanced-level nurses. The primary outcome is the Trial Outcome Index of the Functional Assessment of Cancer Therapy (FACT) at 12 weeks. The secondary outcomes include participants' quality of life (FACT-Lung), depression (Patient Health Questionnaire-9), anxiety (Generalized Anxiety Disorder-7), illness perception (Prognosis and Treatment Perceptions Questionnaire), medical service use and survival. A mixed-method approach is expected to provide an insight about how this intervention works. Ethics and dissemination: This study has been approved by the Institutional Review Board of the National Cancer Center Japan (approval number: 2016-235). The findings will be disseminated through peer-reviewed publications and conference presentations and will be reflected on to the national healthcare policy. Trial registration number: UMIN000025491.